Οἱ ἰατροὶ λέγουσι … – Erläuterungen zur anatomischen Terminologie in Περὶ τῆς τοῦ ἀνθρώπου κατασκευῆς - Grimm-Stadelmann, Isabel (Byzantinische Zeitschrift, 2019)
The anatomical and physiological treatise Περὶ τῆς τοῦ ἀνθρώπου ἀνθρώπου κατασκευῆς is characterized by a peculiarity of medical terminology which is largely unknown from comparable texts: on the one hand, anatomical terms are put into relation with corresponding terms from poetic language, on the other hand they are precisely defined by descriptions of objects of everyday use. The considerable discrepancy between the Greek original and its Latin translation is of particular interest against the background of the renaissance of Περὶ τῆς τοῦ ἀνθρώπου κατασκευῆς in the 16th century AD. The multiple versions of the Latin translation show that medical terminology in Latin language was still in an ongoing process of development, for which reason many Greek anatomical terms were inserted untranslated into the Latin text due to a lack of an adequate Latin equivalents. For this reason Περὶ τῆς τοῦ τοῦ ἀνθρώπου κατασκευῆς plays a central role in the development of anatomical terminology, but also in its becoming more and more specific and precise.null